Nurse perceptions of the impact of nursing care on patient outcomes: An exploratory study - Schreuders, L.; Bremner, A.; Geelhoed, E.; Finn, Judith (eContent Management, 2012)
The aim of this research was to explore registered nurses’ perceptions of the relationship between nursing care and clinical outcomes. We conducted an exploratory survey using a convenience sample of nurses attending a 3 day nursing practice conference. Nurses with postgraduate degrees and those with a clinical main work role had higher mean scores for the impact of nursing care on patient outcomes. Nurses reported that pressure ulcers and surgical wound infection were most affected by nursing care. Falls, medication errors, pain management, and patient education were some of the clinical indicators suggested as additional appropriate measures of nursing care. Our results suggest that nurses’ educational background and work role may influence their perception of the impact of nursing care on patient outcomes.